MASSIVE PLEURAL EFFUSION AS AN RESULT OF HEREDITARY MULTIPLE EXOSTOSES - Kocev, Smiljana Bundovska; Antuleska-Belceska, Gordana (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
Hereditary multiple exostoses (HME) is a rare, benign autosomal dominant genetic disorder, but in very rare cases they can have malignant transformation. Exostoses can cause pain, pressure on some nerves, blood vessels and damage on surrounding tissues. Chest CT and CT angiography play an indispensable role in the diagnoses and management of exostoses. We report an eleven-year-old boy with massive pleural effusion caused by costal exostoses on the right ninth rib. Costal exostoses represent an unusual cause of pleural effusion. Key words : Costal exostosis, hereditary multiple exostoses, osteochondroma, pleural effusion. https://doi.org/10.55302/JMS2143049bk